Keputusan Konsumen Dalam Memilih Hotel Syariah: Ditinjau Dari Halal Lifestyle, Muslim Friendly Facilities, Dan Knowledge - Diah Aprilianing Tyas; Agus Supriyanto (LPPM ISNJ Bengkalis, 2022)
This study aims to empirically show the effect of a halal lifestyle, Muslim-friendly facilities, and knowledge on consumer decisions in choosing sharia hotels. This research is field research with a quantitative approach. The research population is the customers of the Abbas Syariah Kudus hotel, but the number still needs to be determined. The sampling technique used purposive sampling with a sample of 115 respondents. The data analysis technique uses multiple linear regression with the help of the SPSS program. The study results show that a partially halal lifestyle, Muslim-friendly facilities, and knowledge positively and significantly affect sharia hotel consumer decisions. This research can complement existing theories. Practically, this research can be used as a reference for sharia hotel business people to pay attention to the halal lifestyle, Muslim-friendly facilities, and knowledge to win customers' hearts.